(untitled) (CIPEEX, 2025)
Introduction: Most women complain of vaginal infections, which account for 40% of gynecological consultations. During pregnancy, vulvovaginitis is associated with unfavorable obstetric outcomes. Objective: The objective of this study was to recognize the scientific evidence on the relationship between pathological vaginal discharge and the risk of complications during pregnancy. Methodology: This is a scoping review guided by the question: What is the scientific evidence on pathological vaginal discharge and complications in pregnancy? Scientific articles were collected from the PubMed, BVS, and SciELO databases. Results: Of the 35 articles analyzed, 10 were selected to compose the final sample. It was evident that pathological vaginal discharge is a very common occurrence in pregnancy and that treatment is necessary whenever diagnosed in order to prevent harm to the mother and baby. Conclusion: It can therefore be seen that the studies addressed in this scoping review provide scientific evidence of a relationship between pathological vaginal discharge and the risk of complications during pregnancy.